Accumulated neighbourhood deprivation and coronary heart disease: a nationwide cohort study from Sweden. Issue 9 (17th September 2019) - Lönn, Sara Larsson; Melander, Olle; Crump, Casey; Sundquist, Kristina
Abstract : Objective: Neighbourhood deprivation is a recognised predictor of coronary heart disease (CHD). The overall aim was to investigate if accumulated exposure to neighbourhood deprivation resulted in higher odds of CHD. Design: This is a longitudinal cohort study. Models based on repeated assessments of neighbourhood deprivation as well as single-point-in-time assessments were compared. Setting: Sweden. Participants: 3 140 657 Swedish men and women without a history of CHD and who had neighbourhood deprivation exposure data over the past 15 years. Primary outcome measures: CHD within 5 years' follow-up. Results: The results suggested a gradient of stronger association with CHD risk by longer cumulative exposures to neighbourhood deprivation, particularly in the younger age cohorts. Neighbourhood deprivation was also highly correlated over time, especially in older age cohorts. Conclusions: The effect of neighbourhood deprivation on CHD might depend on age. Accounting for individuals' baseline age may therefore be important for understanding neighbourhood environmental effects on the development of CHD over time. However, because of high correlation of neighbourhood deprivation over time, single-point-in-time assessments may be adequate for CHD risk prediction especially in older adults.